A bibliometric analysis of reward-based crowdfunding related research: current trends and future prospect - Fatma Tatli Kalayci; Hasan Aydin Okuyan (Future Business Journal)
Abstract The primary objective of this research pertains to conducting a bibliometric examination of articles accessible within the Web of Science database that pertain to reward-based crowdfunding. This research was conducted over a corpus of 261 publications spanning the timeframe of 2014 to 2023, from the WoS database. The results of the research revealed a notable trend of reward-based crowdfunding researchers. The research also sought to identify key authors, institutions, journals, and countries that hold paramount significance for future scholars delving into the study of reward-based crowdfunding, consequently delineating fundamental thematic underpinnings. The insights gleaned from these analyses are anticipated to offer valuable guidance to researchers engaging in explorations within this particular domain. The meticulous evaluation of publications and their interconnections sheds light on prevalent trends, influential contributors, and core topics, thereby furnishing a compass for prospective research endeavors.